CiRS‐7 targeting miR‐7 modulates the progression of non‐small cell lung cancer in a manner dependent on NF‐κB signalling - Su, Chongyu (J Cell Mol Med, 2018)
The purpose of this study was to figure out the effect of ciRS‐7/miR‐7/NF‐κB axis on the development of non‐small cell lung cancer (NSCLC). In response, the expressions of ciRS‐7, miR‐7 and NF‐κB subunit (ie RELA) within NSCLC tissues and cell lines were determined with real‐time polymerase chain reaction (RT‐PCR) and Western blot. Moreover, the NSCLC cells were transfected with pcDNA3‐ciRS‐7‐ir, pcDNA3‐ciRS‐7, miR‐NC and miR‐7 mimic. Furthermore, the targeted relationships between ciRS‐7 and miR‐7, as well as between miR‐7 and RELA, were confirmed by luciferase reporter assay. The proliferation, migration and apoptosis of NSCLC cells were, successively, measured using CCK‐8 assay, wound‐healing assay and flow cytometry test. Consequently, ciRS‐7, miR‐7, histopathological grade, lymph node metastasis and histopathological stage could independently predict the prognosis of patients with NSCLC (all P < .05). Moreover, remarkably up‐regulated ciRS‐7 and RELA expressions, as along with down‐regulated miR‐7 expressions, were found within NSCLC tissues and cells in comparison with normal ones (P < .05). Besides, overexpressed ciRS‐7 and underexpressed miR‐7 were correlated with increased proliferation, migration and invasion, yet reduced apoptosis rate of NSCLC cells (P < .05). More than that, ciRS‐7 specifically targeted miR‐7 to reduce its expressions (P < .05). Ultimately, the NSCLC cells within miR‐7 + RELA group were observed with superior proliferative, migratory and invasive capabilities than those within miR‐7 group (P < .05), and RELA expression was also significantly modified by both ciRS‐7 and miR‐7 (P < .05). In conclusion, the ciRS‐7/miR‐7/NF‐kB axis could exert pronounced impacts on the proliferation, migration, invasion and apoptosis of NSCLC cells.